SUBSTITUSI TEPUNG TERIGU DENGAN TEPUNG AMPAS KEDELAI PADA PRODUK COOKIES YANG KAYA AKAN SERAT PANGAN DAN PROTEIN - Novy Nur Adhimah; Ade Heri Mulyati; Diana Widiastuti (Universitas Pakuan, 2017)
Soybean waste is one of the alternative sources of fiber which is a by-product in the manufacture of tofu and contains high crude protein. Fiber and protein are given in the form of soybean pulp with variation of 0-40%. This study aims to determine the addition of maximal soybean pulp that provides the properties of cookies that can be accepted by the public and to know the physical properties, microbiology, chemistry including food fiber. The best soybean dregs flour is without washing, steaming. Soybean flour without washing, steaming has 11.65% water content, 3.15% ash, 18.37% protein, 1.25% total food fiber, 0.94% insoluble food fiber, 0 soluble food fiber, 31%, lead 0.04 ppm, cadmium 0.005 ppm, and zinc 20.80ppm, total plate counts (ALT) of 2 x 102 kol / gram, E.coli 3 AMP / gram, / gram. Cookies C5 with the ratio of soybean flour and wheat flour (40%: 60%) are selected products, physical characteristics of soybean cookies include color parameters, aroma, crispness and flavor. The result of analysis of nutrient content of cookies obtained by water content 2,22%, ash 2.20%, protein 7.2%, total food fiber (TDF) 0.85%, insoluble food fiber (IDF) 0,51, soluble (SDF) 0.33%, zinc 25.60 ppm, lead 0.04 ppm, cadmium 0.005 ppm Total total plate count (ALT) of 25 x 10-1 cab / gram, E.coli 3 AMP / gram, mold 10 kol / gram.Key words : Food Disversivication, Soybeans, Cookies, Proteins, Food Fiber